2017
DOI: 10.21886/2219-8075-2017-8-2-23-29
|View full text |Cite
|
Sign up to set email alerts
|

Association of COL1A1 gene -1997 C>A (rs1107946) polymorphism with bone mineral density in postmenopausal women

Abstract: Ассоциации полиморфизма -1997 C>A (rs1107946) гена COL1A1 с минеральной плотностью костной ткани у женщин в постменопаузальном возрасте Э.А. Майлян Донецкий национальный медицинский университет им. М. Горького, Донецк, УкраинаЦель: изучить показатели минеральной плотности кости в зоне поясничных позвонков L1-L4 и проксимальных отделов левой и правой бедренных костей, в том числе шеек левого и правого бедра, у женщин в постменопаузальном возрасте в зависимости от генотипов полиморфизма -1997 C>A гена COL1A1. Ма… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The authors found that osteoporotic changes in the femoral neck were significantly more pronounced in women with A allele (OSH = 2.46, 95% CI: 1.38-4.39, p = 0.006). In addition, in the group of patients with osteoporosis of the left femoral neck in comparison with all other women, a somewhat unreliable tendency (p = 0.064) to an increased accumulation of the AA genotype was established [13].…”
Section: Discussionmentioning
confidence: 89%
“…The authors found that osteoporotic changes in the femoral neck were significantly more pronounced in women with A allele (OSH = 2.46, 95% CI: 1.38-4.39, p = 0.006). In addition, in the group of patients with osteoporosis of the left femoral neck in comparison with all other women, a somewhat unreliable tendency (p = 0.064) to an increased accumulation of the AA genotype was established [13].…”
Section: Discussionmentioning
confidence: 89%